2020
DOI: 10.1016/j.molcel.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

4D Genome Rewiring during Oncogene-Induced and Replicative Senescence

Abstract: Highlights d Deep multi-omics characterization of replicative and oncogene-induced senescence d Senescence-associated heterochromatin domains (SAHDs) form SAHFs via 3D changes d DNMT1 is required for SAHF formation via regulation of HMGA2 expression d SAHF formation leads to expression of SAHF-adjacent genes via 3D chromatin contacts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
161
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(183 citation statements)
references
References 81 publications
19
161
3
Order By: Relevance
“…Imaging studies have reported decondensation at chromocenters after Dnmt1 KO in mouse embryonic fibroblasts (Casas-Delucchi et al, 2012) and an increase in DNase-I sensitivity of the inactive X chromosome after 5-azacytidine treatment of gerbil lung fibroblasts (Jablonka et al, 1985). More recently, loss of compartmentalisation was found in senescent fibroblasts with DNMT1 knockdown (Sati et al, 2020). In contrast, a prior study using the HCT116 DKO1 hypomethylation cell model did not find an increase in genome-wide open chromatin, suggesting no chromosomal de-condensation (Pandiyan et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Imaging studies have reported decondensation at chromocenters after Dnmt1 KO in mouse embryonic fibroblasts (Casas-Delucchi et al, 2012) and an increase in DNase-I sensitivity of the inactive X chromosome after 5-azacytidine treatment of gerbil lung fibroblasts (Jablonka et al, 1985). More recently, loss of compartmentalisation was found in senescent fibroblasts with DNMT1 knockdown (Sati et al, 2020). In contrast, a prior study using the HCT116 DKO1 hypomethylation cell model did not find an increase in genome-wide open chromatin, suggesting no chromosomal de-condensation (Pandiyan et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Whether these topological changes are related to changes in the levels of chromatin-bound CTCF or cohesin remains to be tested. Furthermore, a subset of genes activated upon OIS are located adjacent in the linear genome to regions that form SAHF and depend on SAHF formation to engage in TSS-TSS interactions that enhance their transcription (Sati et al, 2020), therefore heterochromatin repositioning during senescence causes upregulation of nearby genes by altering their interaction profiles.…”
Section: Senescence-associated Heterochromatin Focimentioning
confidence: 99%
“…Pioneer transcription factors (that directly bind condensed chromatin) are critical in establishing new cell fate competence: they grant longterm chromatin access to non-pioneer factors and help determine cell identity by opening and licensing the enhancer landscape [68,70,71]. In addition, DNA methylation could play an important role in establishment of senescence as recently was shown for a DNMT1dependent downregulation of BRCA1/ZNF350/RBBP8 repressor complex in the course of oncogene-induced senescence [72]. Thus, efforts to identify different factors and the signaling pathways that they control could be critical in understanding the feasibility of rejuvenating senescent LSECs as a therapeutic strategy.…”
Section: Reprogramming Senescent Lsecsmentioning
confidence: 99%